Deformation rule of light area reduction shafts by cross wedge rolling - LIU Wen-ke; ZHANG Kang-sheng; YANG Guang; HU Zheng-huan (工程科学学报)
The forming process of shafts by cross wedge rolling (CWR) was presented by numerical simulation and rolling experiment. The metal deformation characteristics of roiled pieces were studied from the view of area reduction. It is found that the cut-off point between rolled pieces with light area reduction and conventional area reduction is roughly at 35%. Comparative analysis was mainly focused on the deformation rule of rolled pieces with light area reduction and conventional area reduction. The results show that the main deformation of roiled pieces with light area reduction is near the outer while that with conventional area reduction is inside. A more uneven axial tensile deformation exists in rolled pieces with light area reduction than in rolled pieces with conventional area reduction, leading to a heavier cross section elliptical deformation in rolled pieces with light area reduction.